Inhibition of Bone Loss by Cissus quadrangularis in Mice: A Preliminary Report. (21st June 2012) - Banu, Jameela; Varela, Erika; Bahadur, Ali N.; Soomro, Raheela; Kazi, Nishu; Fernandes, Gabriel
Abstract : Women drastically loose bone during and after menopause leading to osteoporosis, a disease characterized by low bone mass increasing the risk of fractures with minor trauma. Existing therapies mainly reduce bone resorption, however, all existing drugs have severe side effects. Recently, the focus is to identify alternative medicines that can prevent and treat osteoporosis with minimal or no side effects. We used Cissus quadrangularis (CQ), a medicinal herb, to determine its effects on bone loss after ovariectomy in C57BL/6 mice. Two-month old mice were either sham operated or ovariectomized and fed CQ diet. After eleven weeks, mice were sacrificed and the long bones scanned using pQCT and μ CT. In the distal femoral metaphysis, femoral diaphysis, and proximal tibia, control mice had decreased cancellous and cortical bone, while CQ-fed mice showed no significant differences in the trabecular number, thickness, and connectivity density, between Sham and OVX mice, except for cortical bone mineral content in the proximal tibia. There were no changes in the bone at the tibio-fibular junction between groups. We conclude that CQ effectively inhibited bone loss in the cancellous and cortical bones of femur and proximal tibia in these mice.